X-ray radiation of highly charged ions: with 52 tables - Beyer, Heinrich F.; Kluge, Heinz-Jürgen; Ševelʹko, Vjačeslav P. (Springer, 1997)
X-Ray Radiation of Highly Charged Ions is a comprehensive collection of atomic characteristics of highly charged ion (HCI) sources and elementary processes related to X-ray radiation: energy levels, wavelengths, transition probabilities, cross sections, and rate coefficients. The material covers a broad range of elementary processes occuring in hot laboratory and astrophysical plasmas: radiative and dielectronic recombination, radiative electron capture, radiation transfer and excitation, and others. The book comprises a large amount of figures, tables, simple formulas, and if possible scaling laws for radiative and collisional characteristics of HCI. The data presented is useful for specialists who deal with X-ray spectroscopy, physics of HCI, heavy-particle collisions, and thermonuclear fusion
Keywords: Röntgenspektroskopie; Mehrfach geladenes Ion